Herpetofauna of protected areas in the Caatinga II: Serra da Capivara National Park, Piauí, Brazil - Calvacanti, Lucas Barbosa de Queiroga (2014)
We provide a list of amphibians, lizards, chelonians, and snakes collected during a 30-day expedition to the Serra da Capivara National Park, Piauí State, Brazil. Thirty-seven pitfall trap arrays composed of 4 buckets each, along with glue traps, funnel traps, and haphazard searches, were used to sample the herpetofaunal diversity. We recorded 17 species of lizards, 1 caecilian, 1 chelonian, 7 frogs, and 11 snakes. Rarefaction curves suggest that local biodiversity is still underestimated. An atypical drought during the period of study may have contributed to lower captures of certain groups, especially amphibians and snakes. The presence of water-dependent and forest-dependent species within local canyons (“Boqueirões”) suggests that these areas harbor faunas associated with relictual rainforest fragments and need to be better studied and managed accordingly